2005
DOI: 10.1152/ajplung.00397.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human airway epithelial cells produce IP-10 (CXCL10) in vitro and in vivo upon rhinovirus infection

Abstract: Human rhinovirus (HRV) infections trigger exacerbations of asthma and chronic obstructive pulmonary disease (COPD) and are associated with lymphocytic infiltration of the airways. We demonstrate that infection of primary cultures of human airway epithelial cells, or of the BEAS-2B human bronchial epithelial cell line, with human rhinovirus type 16 (HRV-16) induces expression of CXCL10 [IFN-gamma-inducible protein 10 (IP-10)], a ligand for the CXCR3 receptor found on activated type 1 T lymphocytes and natural k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
299
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(322 citation statements)
references
References 38 publications
23
299
0
Order By: Relevance
“…In our studies of TON, sterile inflammation occurs in the absence of live pathogens, and we found that CXCL10 up-regulation is associated with STAT1 and STAT3 activation and its production is significantly attenuated by blocking STAT1 and STAT3 activation with Stattic. In contrast, NF-kB, a proinflammatory transcription factor regulating CXCL10 expression after viral infection, 51,52 does not participate in axonal injury-induced CXCL10 expression. To our knowledge, this is the first report that provides evidence suggesting that STAT1 and STAT3 appear to regulate CXCL10 level during sterile inflammation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In our studies of TON, sterile inflammation occurs in the absence of live pathogens, and we found that CXCL10 up-regulation is associated with STAT1 and STAT3 activation and its production is significantly attenuated by blocking STAT1 and STAT3 activation with Stattic. In contrast, NF-kB, a proinflammatory transcription factor regulating CXCL10 expression after viral infection, 51,52 does not participate in axonal injury-induced CXCL10 expression. To our knowledge, this is the first report that provides evidence suggesting that STAT1 and STAT3 appear to regulate CXCL10 level during sterile inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…Sequence analysis revealed that the CXCL10 promoter region contains transcription factor binding sites for AP-1, NF-kB, interferon regulatory factor, and STAT. 51,52 Because activation of NF-kB has an essential role in inflammatory reactions and has been shown to induce CXCL10 expression during virus infection, 51 Quantitative PCR analysis of CXCR3 mRNA expression in control or injured retinas at 3, 6, 12, and 24 hours after TON. E: Representative images of CXCR3 immunostaining in retinal frozen sections from control and TON-performed eyes at 24 hours after TON.…”
Section: Up-regulation Of Cxcl10 In Ton Is Mediated By Statmentioning
confidence: 99%
“…The anatomical compartment chosen for this recruitment assay is the airways, as both IP-10 and I-TAC, as well as other chemokines, have been shown to be expressed by bronchial epithelial cells especially during various inflammatory diseases, such as tuberculosis , chronic obstructive pulmonary disease (COPD) (Saetta et al, 2002), and rhinovirus infections (Spurrell et al, 2005), resulting in the recruitment of CXCR3 + lymphocytes into the airways. By instilling I-TAC or IP-10 directly into the airways, this assay models the natural environment in which these chemokines are normally expressed during inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…5A) (34). Data are expressed as fold difference, as little and no significant difference was observed in baseline levels observed between each construct when nonstimulated (data not shown).…”
Section: Essential Elements In the Human Cxcl10 Promoter Region In Rementioning
confidence: 99%